Transformasi Positif: Implementasi Pendidikan Karakter berbasis Budaya di SD Muhammadiyah Sapen - Rahmah Kumullah; Puji Yanti Fauziah; Lutfi Wibawa; Ismu Sukamto (STKIP Andi Matappa Pangkep, 2023)
This research aims to explain how character education is implemented in the learning process and identify factors that support and hinder the implementation of character education at SD Muhammadiyah Sapen, Yogyakarta City. The approach used in this study is qualitative. Data was collected through various methods such as in-depth interviews, observation, and documentation, and then analyzed descriptively and qualitatively. The research results show that character education at this school is involved in all subjects, extracurricular activities, and routine habits. It is hoped that the results of this research can provide benefits for educators and education staff in inspiring innovations that can improve the quality of learning that focuses on building student character.